CONTRIBUTIONS TO THE STUDY OF MILK QUALITY FROM VARIOUS CATTLE BREEDS - CLAUDIA PÂNZARU; RĂZVAN MIHAIL RADU-RUSU; MARIUS GHEORGHE DOLIȘ; MARIANA NISTOR; VASILE MACIUC; MĂDĂLINA ALEXANDRA DAVIDESCU (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of this study is to compare the milk quality from different cattle breeds (Bălțată cu Negru Românească, Brună de Maramureș, and Bălțată Românească) raised under identical conditions in Romania. The highest values for protein, fat, and lactose content were recorded on Farm II, where the Brună de Maramureș breed is raised: 3.72 ± 0.05 % for protein, 4.61 ± 0.16 % for fat and 4.87 ± 0.04 % for lactose. Additionally, the lowest somatic cell count (SCC) was observed on Farm II at 157.60 ± 16.91 thousand·mL-1 , indicating excellent milking hygiene, with a pH value of 6.61 ± 0.04. Enhancing feed quality and maintaining hygiene practices in shelters and milking parlors can improve milk quality, increase economic efficiency, and promote cow health. Effective selection, breeding, and nutrition management are essential for optimizing milk quality and sustaining a healthy and productive dairy herd.